2021
DOI: 10.1021/acs.est.0c06881
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering on a Ti4O7 Electrode by Ce3+ Doping for the Efficient Electrooxidation of Perfluorooctanesulfonate

Abstract: Defect engineering in an electrocatalyst, such as doping, has the potential to significantly enhance its catalytic activity and stability. Herein, we report the use of a defect engineering strategy to enhance the electrochemical reactivity of Ti 4 O 7 through Ce 3+ doping (1− 3 at. %), resulting in the significantly accelerated interfacial charge transfer and yielding a 37− 129% increase in the anodic production of the hydroxyl radical (OH • ). The Ce 3+ -doped Ti 4 O 7 electrodes, [(Ti 1−x Ce x ) 4 O 7 ], als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…One recent study indicated that Ce 3+ doping on a Ti 4 O 7 anode enhanced the electrooxidation of PFOS and attributed it to increased surficial oxygen vacancies. 30 Other possible dopants could be selected among elements such as Co, Pt, Mo, Ta, W, Y, and Zr by the computation strategies and criteria developed in this study. The destruction of PFASs in water, short chain PFAAs in particular, is challenging for the purpose of treatment.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…One recent study indicated that Ce 3+ doping on a Ti 4 O 7 anode enhanced the electrooxidation of PFOS and attributed it to increased surficial oxygen vacancies. 30 Other possible dopants could be selected among elements such as Co, Pt, Mo, Ta, W, Y, and Zr by the computation strategies and criteria developed in this study. The destruction of PFASs in water, short chain PFAAs in particular, is challenging for the purpose of treatment.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…29 In addition to having all of the properties required for an anode used for water treatment, TSO anodes are relatively facile to fabricate at low costs. 30 Ti 4 O 7 has the highest conductivity (1500 S cm −1 ) among all TSOs, comparable to graphite, and has been studied for EO applications. 31 Recent studies have demonstrated the great performance of Ti 4 O 7 -based EO in degrading a wide variety of organic contaminants, 32 including substituted phenols, 33 tetracycline, 34 trichloroethylene, 35,36 amoxicillin, 37 and chloroform, 36 as well as disinfecting pathogens and viruses.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cost analysis demonstrated that Ti 4 O 7 electrodes were cheaper to synthesize relative to boron‐doped diamond, at ~$0.36 per m 2 versus ~$7125 per m 2 (Chaplin, 2019). Although Ti 4 O 7 are cheaper to produce than boron‐doped diamond, they are not without limitation; for example, Ti 4 O 7 electrodes are a nascent technology with shorter electrode lifespans than boron‐doped diamond (Huang et al, 2020; Lin et al, 2021; Stirling et al, 2020). Thus, more research on extending electrode lifespan and stability relative to boron‐doped diamond electrodes is essential to facilitate implementation in water treatment applications.…”
Section: Electrochemical Treatment As a Pfas Mitigation Technologymentioning
confidence: 99%
“…Reactive oxygen species (ROS, i.e., • OH, O 2 •– , and SO 4 •– ) with one or more unpaired electrons have attracted much attention in various fields, including oil rancidification, food spoilage, and organic degradation. , The high oxidation potential of ROS breaks Si–O–Si bonds (with energy barrier of 4 kcal/mol in aluminosilicate gel) and increases the crystallization rate for zeolite growth at low temperatures. Recently, Yu et al proposed that • OH could accelerate the crystallization process of zeolite by catalyzing the depolymerization of the aluminosilicate gel and reforming the Si, Al–O–Si, and Al bonds .…”
Section: Introductionmentioning
confidence: 99%